Hydrogenation of cinnamaldehyde to hydrocinnamaldehyde over Pd nanoparticles deposited on nitrogen-doped mesoporous carbon - Nagpure, Atul S.; Gurrala, Lakshmiprasad; Gogoi, Pranjal; Chilukuri, Satyanarayana V. (RSC Advances, 2016)
Palladium nanoparticles deposited on nitrogen-doped mesoporous carbon (NMC) were synthesized by simple ultrasonic-assisted method. This novel Pd-NMC catalyst was highly active and selective for the hydrogenation of cinnamaldehyde (CA) to hydrocinnamaldehyde (HCA) at room temperature (30 degrees C) under low H-2 pressure. The nitrogen-free mesoporous carbon (MC) and activated carbon (AC) were also employed as the support for Pd in the liquid-phase hydrogenation of CA. The incorporation of nitrogen into carbon matrix remarkably enhanced the catalytic activity and C=C bond hydrogenation selectivity (HCA selectivity of 93% with 100% CA conversion for Pd-NMC) in CA hydrogenation compared to the catalysts with no nitrogen (HCA selectivity of 66 and 47% for Pd-MC and Pd-AC, respectively). Moreover, Pd-NMC catalyst demonstrated an excellent recyclability without any loss in activity and HCA selectivity when it was reused for six times. The superior catalytic performance of Pd-NMC catalyst in CA hydrogenation is attributed to the small size of Pd nanoparticles due to presence of high nitrogen content (11.6 wt%) and mesoporous nature of NMC support.